Retrospective Study of Appropriate Primary Prevention in Postmenopausal Women Presenting with a Major Adverse Cardiovascular Endpoint (MACE) - Nicole E. Cieri-Hutcherson; Aleksandra Lomakina; Maya R. Chilbert (MDPI AG, 2022)
Background: Postmenopausal women may be at an increased risk for cardiovascular events. The postmenopausal transition represents a key time for implementation of preventative strategies to reduce the risk of cardiovascular disease. The objective of this study was to evaluate the appropriate use of primary prophylaxis of cardiovascular disease in this population and to determine if an opportunity exists for improvement in primary prevention prescribing. Methods: A single-center, retrospective study was conducted of postmenopausal women aged 45-60 years between 1 October 2019 and 30 April 2021 with a diagnosis of a new major adverse cardiovascular event (MACE). This study was approved by the University at Buffalo Institutional Review Board. Results: After application of inclusion and exclusion criteria, 231 patients were included and analyzed. Median age was 55 years; 66.6% white; median body mass index was 30.11 kg/m2; 30.3% history of diabetes; 51.1% current smokers; 82.3% with a primary care provider (PCP); 97.6% insured. Patients with diabetes, current smokers, and those without a PCP were more likely to have inappropriate primary prevention use than patients without diabetes, non-smokers, and with a PCP, respectively (78.7% vs. 51.3%, p = 0.0002; 57.6% vs. 42.4%, p = 0.0177; 73.7% vs. 56.0%, p = 0.0474). Specifically, current smokers, and those with diabetes had significantly more inappropriate use of aspirin and statins for primary prevention than non-smokers and patients without diabetes. Conclusions: This study observed the use of appropriate primary prevention therapies in postmenopausal women and found that an opportunity may exist to improve prescribing appropriate primary prevention therapies for certain groups, most notably in postmenopausal women with diabetes, smokers, uninsured, and those without a PCP.